Time-course of changes in key catecholaminergic receptors and trophic systems in rat brain after antidepressant administration. (December 2020) - Kusmider, M.; Faron-Górecka, A.; Solich, J.; Pabian, P.; Dziedzicka-Wasylewska, M.
Abstract: Several biochemical parameters within the brain are altered by antidepressants. However, it is still uncertain which parameters are important for the evaluation of the effectiveness of these drugs. What seems certain is that the response of the nervous system is dynamic. The dynamic nature of the nervous system is still poorly understood, although it has implications in clinical management. Criteria for evaluating treatment resistant depression are based on this temporal variability. The present study was designed to evaluate dynamic alterations in catecholaminergic receptors and calcyon (associated with monoaminergic theory of depression) in the rat brain as well as brain-derived neurotrophic factor (BDNF) and tyrosine kinase beta (TRKB; related to neurotrophin theory) induced by three antidepressant drugs (ADs) with various pharmacological profiles (imipramine, desipramine, and citalopram) administered for 21 days or acutely, followed by various drug-free periods. Receptor autoradiography and in situ hybridization studies allowed us to identify changes in various brain regions simultaneously in each rat. Repeated treatment with ADs induced biochemical alterations, which were in agreement with the results of previous studies. These alterations include the downregulation of β1, β2, and α1 adrenergic receptors, upregulation of α2-adrenergic receptors and dopamine D2 receptors, and increased expression of BDNF in the hippocampus. Additionally, we observed dynamic alterations in the measured parameters after acute drug administration, particularly at the level of dopamine receptors, which were extremely sensitive to a single dose of ADs followed by various drug-free periods. All three ADs induced the upregulation of dopamine D2 receptor mRNA levels in the nucleus accumbens. The same effect was induced by single doses of ADs followed by various drug-free periods. The obtained results indicate that alterations in the availability of neurotransmitters at synapses induced by ADs are strong enough to induce immediate and long-lasting adaptive changes in the neuronal network. Highlights: In rats, a single administration of antidepressants exerts some delayed biochemical effects. Time-course of changes in several biochemical parameters reveals differences between citalopram and classic antidepressants. These data support the use of pulse therapy for the delivery of antidepressants during treatment for depression.